MgCl2·6H2O catalyzed highly efficient synthesis of 2-substituted-1H-benzimidazoles. Issue 21 (20th May 2015) - Ghosh, Pranab; Subba, Raju
Graphical abstract: Abstract: A series of substituted benzimidazoles were efficiently prepared by combining 1, 2-phenylenediamine with aryl, heteroaryl aldehydes in the presence of catalytic amount of MgCl2 ·6H2 O. The advantages of this new protocol are high conversion, clean reaction profile, use of less toxic catalyst, low cost, and environment friendly. The method is very simple mild and applicable to aryl as well as heteroaryl aldehydes without significant difference.